A q product integral

Calculus Level 5

0 1 k = 1 ( 1 q k ) d q = ? \int _{ 0 }^{ 1 }{ \prod _{ k=1 }^{ \infty }{ { \left( 1-{ q }^{ k } \right) }\ dq } } = ?

Express your solution up to 3 decimal places.


The answer is 0.3684125.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Patrick Corn
Jan 22, 2019

The integrand is famously equal to n = ( 1 ) n q ( 3 n 2 n ) / 2 . \sum\limits_{n=-\infty}^\infty (-1)^n q^{(3n^2-n)/2}. (You can find a proof here .)

Integrating gives 1 + n 0 2 3 n 2 n + 2 ( 1 ) n = 1 + n = 1 ( 1 ) n ( 2 3 n 2 n + 2 + 2 3 n 2 + n + 2 ) 1 + \sum_{n \ne 0} \frac2{3n^2-n+2} (-1)^n = 1 + \sum_{n=1}^\infty (-1)^n \left( \frac2{3n^2-n+2} + \frac2{3n^2+n+2} \right) and this is easily evaluated by your favorite computer package to be approximately 0.368413 . \fbox{0.368413}.

beautiful, however with my method i get a divergence to 0. can anyone help?

Jason Rice - 2 years, 4 months ago

The exact expression is very ugly but it is expressable with elementary functions:

8 69 π sinh ( 23 π 6 ) 23 ( 1 + 2 cosh ( 23 π 3 ) ) \frac{8 \sqrt{69} \pi \sinh{\left (\frac{\sqrt{23} \pi}{6} \right )}}{23 \left(-1 + 2 \cosh{\left (\frac{\sqrt{23} \pi}{3} \right )}\right)}

D G - 2 years, 4 months ago

Log in to reply

@D G Proof please.........

Aaghaz Mahajan - 2 years, 4 months ago
Syed Shahabudeen
Jan 22, 2019

The following infinite product can be represented in a q pochammer symbol form i.e k = 1 ( 1 q k ) = ( q ; q ) \prod _{ k=1 }^{ \infty }{ \left( 1-{ q }^{ k } \right) } ={ \left( q;q \right) }_{ \infty } we know that the ramanujan theta function is defined as f ( a , b ) = n = a n ( n + 1 ) 2 b n ( n 1 ) 2 = ( a ; a b ) ( b ; a b ) ( a b ; a b ) f\left( a,b \right) =\sum _{ n=-\infty }^{ \infty }{ { a }^{ \frac { n(n+1) }{ 2 } }{ b }^{ \frac { n(n-1) }{ 2 } } } ={ \left( -a;ab \right) }_{ \infty }{ \left( -b;ab \right) }_{ \infty }{ \left( ab;ab \right) }_{ \infty } when a = q a =-q and b = q 2 b={ -q }^{ 2 } we have f ( q , q 2 ) = n = ( 1 ) n q n ( 3 n 1 ) 2 = ( q ; q 3 ) ( q 2 ; q 3 ) ( q 3 ; q 3 ) f\left( -q,{ -q }^{ 2 } \right) =\sum _{ n=-\infty }^{ \infty }{ { \left( -1 \right) }^{ n } } { q }^{ \frac { n(3n-1) }{ 2 } }={ \left( q;{ q }^{ 3 } \right) }_{ \infty }{ \left( { q }^{ 2 };{ q }^{ 3 } \right) }_{ \infty }{ \left( { q }^{ 3 };{ q }^{ 3 } \right) }_{ \infty } here the triple infinite product is ( q ; q 3 ) ( q 2 ; q 3 ) ( q 3 ; q 3 ) = k = 0 ( 1 q 3 k + 1 ) ( 1 q 3 k + 2 ) ( 1 q 3 k + 3 ) = ( 1 q 1 ) ( 1 q 2 ) ( 1 q 3 ) ( 1 q 4 ) ( 1 q 5 ) . . . . . . = ( q ; q ) { \left( q;{ q }^{ 3 } \right) }_{ \infty }{ \left( { q }^{ 2 };{ q }^{ 3 } \right) }_{ \infty }{ \left( { q }^{ 3 };{ q }^{ 3 } \right) }_{ \infty }=\prod _{ k=0 }^{ \infty }{ \left( 1-{ q }^{ 3k+1 } \right) \left( 1-{ q }^{ 3k+2 } \right) \left( 1-{ q }^{ 3k+3 } \right) =\left( 1-{ q }^{ 1 } \right) \left( 1-{ q }^{ 2 } \right) \left( { 1-q }^{ 3 } \right) \left( { 1-q }^{ 4 } \right) \left( { 1-q }^{ 5 } \right) ......={ \left( q;q \right) }_{ \infty } } therefore we can write the infinite product as the bilateral infinite series i.e 0 1 n = ( 1 ) n q n ( 3 n 1 ) 2 d q = n = ( 1 ) n 2 3 n 2 n + 2 \int _{ 0 }^{ 1 }{ { \sum _{ n=-\infty }^{ \infty }{ { \left( -1 \right) }^{ n } } { q }^{ \frac { n(3n-1) }{ 2 } } }dq } =\sum _{ n=-\infty }^{ \infty } \frac { { \left( -1 \right) }^{ n }2 }{ { 3n }^{ 2 }-n+2 } by applying residue theorem for infinite series we can evaluate the sum to be 2 3 n = ( 1 ) n ( n ( 1 + i 23 6 ) ) ( n ( 1 i 23 6 ) ) = 2 π i 23 ( cosec ( π ( 1 + i 23 6 ) cosec ( π ( 1 i 23 6 ) ) ) ) = 0.36841... \frac { 2 }{ 3 } \sum _{ n=-\infty }^{ \infty } \frac { { \left( -1 \right) }^{ n } }{ \left( n-\left( \frac { 1+i\sqrt { 23 } }{ 6 } \right) \right) \left( n-\left( \frac { 1-i\sqrt { 23 } }{ 6 } \right) \right) } =\frac { -2\pi }{ i\sqrt { 23 } } \left( \cosec\left( \pi \left( \frac { 1+i\sqrt { 23 } }{ 6 } \right) -\cosec\left( \pi \left( \frac { 1-i\sqrt { 23 } }{ 6 } \right) \right) \right) \right)=0.36841...

Abhishek Sinha
Jan 23, 2019

Start with approximating the product over the range 0 x 1 0\leq x \leq 1 . Use the fact that, for all 0 x 1 0 \leq x \leq 1 , we have 1 x 2 e x 1 x . 1-\frac{x}{2} \geq e^{-x} \geq 1-x. Hence, over the range of integration, the integrand can be bounded as e 2 k = 1 q k k = 1 ( 1 q k ) e k = 1 q k . e^{-2\sum_{k=1}^{\infty} q^k} \leq \prod_{k=1}^{\infty}\big(1-q^k\big) \leq e^{-\sum_{k=1}^{\infty} q^k }. Summing up the geometric series within the exponent, we have e 2 q 1 q k = 1 ( 1 q k ) e q 1 q . e^{-\frac{2q}{1-q}} \leq \prod_{k=1}^{\infty}\big(1-q^k\big) \leq e^{-\frac{q}{1-q}}. Thus, the integral can be upper and lower bounded by integrating the corresponding functions on the right and left. Numerical integration yields that the integral is at least 0.277343 0.277343 and is at most 0.403653 0.403653 . Better approximations yield better bounds.

i did this. but this does not give a good bound.

Srikanth Tupurani - 2 years, 4 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...